The LiaFSR and BsrXRS Systems Contribute to Bile Salt Resistance in Enterococcus faecium Isolates - Zhou, Luoxiong; Wang, Lihong; Tian, Ping; Bao, Tingting; Li, Lianbin; Zhao, Xin (Frontiers in Microbiology, 2019)
Two-component systems (TCSs) are dominant regulating components in bacteria for responding to environmental stimuli. However, little information is available on how TCSs in E. faecium respond to bile salts - an important environmental stimulus for intestinal bacteria. In this study, the gene expression of 2 TCSs, BsrXRS and LiaFSR, was positively correlated with survival rates of different E. faecium isolates during exposure to ox gall. Moreover, gene disruptions of bsrR, bsrS, liaS and liaR significantly reduced the survival rates of E. faecium in the presence of ox gall. Finally, EMSA results indicated that BsrR functioned as a transcription regulator for expression of its own gene as well as lipoate-protein ligase A (lplA). Additional 27 potential target genes by BsrR were revealed through in silico analyses. These findings suggest that BsrXRS and LiaFSR systems play important roles in bile salt resistance in E. faecium.